2007
DOI: 10.1111/j.1525-1438.2006.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic low-grade endometrial stromal sarcoma of clitoris: report of a case

Abstract: Low-grade endometrial stromal sarcoma (ESS) is an uncommon neoplasm, which has a highly recurrent nature. A review of the literature revealed that only one case of low-grade ESS, arising within the vulva from a focus of endometriosis, has been previously published. We describe an additional case of low-grade ESS arising within the vulva and to the best of our knowledge the first report of low-grade ESS metastasized to clitoris. A 46-year-old woman was admitted to our hospital due to a heavy uterine bleeding. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Extrauterine leiomyomata localized in the external genitalia is an uncommon lesion arising from smooth muscle cells around vascular epithelium or erectile tissue [1]. The most common extrauterine sites of the disease are the upper digestive tract or the lower respiratory tract, but if the female genital tract is involved, the most frequent localization is the clitoris [2].…”
Section: Introductionmentioning
confidence: 99%
“…Extrauterine leiomyomata localized in the external genitalia is an uncommon lesion arising from smooth muscle cells around vascular epithelium or erectile tissue [1]. The most common extrauterine sites of the disease are the upper digestive tract or the lower respiratory tract, but if the female genital tract is involved, the most frequent localization is the clitoris [2].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, all cases of ESNs reported in the vulvovaginal region ( Table 1 ) have corresponded to endometrial stromal sarcomas of various grades of differentiation. In at least five cases ( Androulaki et al, 2007 , Berkowitz et al, 1978 , Corpa et al, 2004 , Kondi-Paphitis et al, 1998 , Liu et al, 2013 , Masand et al, 2013 ) the tumors appeared to be primary neoplasms, while the remaining ones were likely to be metastatic in nature ( Irvin et al, 1998 , Kondi-Paphitis et al, 1998 , Liu et al, 2013 , Masand et al, 2013 ), since tumor was also found in pelvic locations, colon and lung. Association with endometriosis, locally or elsewhere, was found in 6 cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is the reason why we made the revision of the cases reported on this localization. We made searches with “vulvovaginal endometrial stromal tumor/sarcoma/nodule”, “vaginal endometrial stromal tumor/sarcoma/nodule” and “vulvar endometrial stromal tumor/sarcoma/nodule” and we only found ten reported cases of sarcomas in the vagina and two in the vulva ( Androulaki et al, 2007 , Berkowitz et al, 1978 , Corpa et al, 2004 , Irvin et al, 1998 , Kondi-Paphitis et al, 1998 , Liu et al, 2013 , Masand et al, 2013 ), half of them being metastases from other sites. Bibliographical analysis demonstrated various types of endometrial stromal sarcoma, often associated to endometriosis, but no cases of stromal nodules like the one we are submitting.…”
Section: Introductionmentioning
confidence: 99%
“…14 Low-grade ESS demonstrates slow growth and an indolent course with a tendency for late recurrence. The 5-year survival rates for low-grade ESS ranges from 67 per cent to nearly 100 per cent, 17 but approximately one-half of patients will develop recurrent disease. [11][12][13] Because there are a limited number of cases of extrauterine ESS, its optimal treatment has not been clearly defined.…”
Section: Discussionmentioning
confidence: 99%